Mercapto propyltrimethoxysilane- and ferrous sulfate-modified nano-silica for immobilization of lead and cadmium as well as arsenic in heavy metal-contaminated soil. (November 2020) - Cao, Pengle; Qiu, Kunyan; Zou, Xueyan; Lian, Mingming; Liu, Peisong; Niu, Liyong; Yu, Laigui; Li, Xiaohong; Zhang, Zhijun
Abstract: Nano-silica as an important part of soil is an ideal carrier of passivator material. In this paper, nano-silica was modified by silane coupling agent containing mercapto group and iron (II) salt to afford an organic-inorganic hybrid containing –S-Fe-S functional group (coded as RNS-SFe) on the surface of nano-silica. Results demonstrate that the RNS-SFe nanoparticle has network-like spheroidal shape and a primary particle size is about 18.0 nm. The RNS-SFe hybrid as a potential immobilization agent for heavy metal in soil shows excellent performance for the remediation of the contaminated soil. Specifically, with a dosage of 3.0% (mass ratio) in the soil, it can immobilize bioavailable Pb, Cd, and As by 97.1%, 85.0%, and 80.1%, respectively. Namely, the RNS-SFe hybrid can transform the bioavailable Pb, Cd, and As into insoluble mercapto metal compounds (–S-Pb-S- and –S-Cd-S-) and less soluble iron arsenate (Fe3 (AsO4 )2, FeAsO4 ) precipitate on the surface of nano-silica particle, thereby reducing the toxicity and mobility of the toxic contaminant fractions. In the meantime, the immobilized products of the Pb, Cd and As fractions have good resistance against acid leaching. These results are contributive to the application of RNS-SFe for the remediation of multi-heavy metal-contaminated soils in field. Graphical abstract: Schematic diagram illustrating the preparation of RNS-SFe nanoscale immobilization agent. Image 1 Highlights: The RNS-SFe possessed excellent immobilization ability towards Pb, Cd and As. The resulting RNS-SFe/heavy metal exhibited good resistance against acid/alkali. The RNS-SFe can promote the conversion of bioavailable heavy metals in soils.